SUMO: A Swiss Army Knife for Eukaryotic Topoisomerases - Sun, Yilun; Nitiss, John L.; Pommier, Yves (Frontiers in Molecular Biosciences, 2022)
Topoisomerases play crucial roles in DNA metabolism that include replication, transcription, recombination, and chromatin structure by manipulating DNA structures arising in double-stranded DNA. These proteins play key enzymatic roles in a variety of cellular processes and are also likely to play structural roles. Topoisomerases allow topological transformations by introducing transient breaks in DNA by a transesterification reaction between a tyrosine residue of the enzyme and DNA. The cleavage reaction leads to a unique enzyme intermediate that allows cutting DNA while minimizing the potential for damage-induced genetic changes. Nonetheless, topoisomerase-mediated cleavage has the potential for inducing genome instability if the enzyme-mediated re-ligation is impaired. Regulation of topoisomerase functions are accomplished by post-translational modifications including phosphorylation, polyADP-ribosylation, ubiquitylation and SUMOylation. These modifications modulate enzyme activity, and likely play key roles in determining sites of enzyme action and enzyme stability. Topoisomerase cleavage and re-ligation are affected by a variety of conditions including the action of small molecules, topoisomerase mutations, and DNA structural forms which permit the conversion of the short-lived cleavage intermediate to persistent DNA-protein crosslink (TOP-DPC). Recognition and processing of TOP-DPCs utilizes many of the same post-translational modifications that regulate enzyme activity. This review focuses on SUMOylation of topoisomerases, which has been demonstrated to be a key modification of both type I and type II topoisomerases. Special emphasis is placed on recent studies that indicate how SUMOylation regulates topoisomerase function in unperturbed cells and the unique roles of SUMOylation plays in repairing damage arising from topoisomerase malfunction.